The “Pre-Fascism” Argument: the Study of Authoritarianism in the 20th Century (from a Catalan-Spanish Viewpoint) - Casassas-Ymbert, Jordi (Journal of Catalan Intellectual History, 2011)
This article presents a state of the art on the analysis of modern anti-parliamentarian phenomena, highlighting the emphasis put on both its precedents and long term triggers, also known as “pre-fascism”. The article first proposes to differentiate between these elements, which directly intervene in the development of such a specific phenomenon of the interwar period, and the ones inherent to the complex crisis of insertion of the democratic system in Western Europe. Secondly, these reflections are applied to the specific Catalonia-Spain case. key words Historiographical revisionism, pre-fascism, history of political thinking, nationalism, Catalonia 20th century.